BMC offices along Mahapalika Marg - Ghosh, Ayan (2023)
Bartle Frere had envisioned Mumbai as urbs primus in Indis as early as the 1840s, when he collaborated with architect Henry Conybeare for building the Afghan Church at Navy Nagar, Colaba. His vision of Mumbai as India's prime city set in motion the Gothic Revival phase, which reached its peak under his patronage and in the last decades of the nineteenth century.